Grubbs–Hoveyda type catalysts bearing a dicationic N-heterocyclic carbene for biphasic olefin metathesis reactions in ionic liquids - Koy, Maximilian; Altmann, Hagen J.; Autenrieth, Benjamin; Frey, Wolfgang; Buchmeiser, Michael R. (Beilstein Journal of Organic Chemistry, 2015)
The novel dicationic metathesis catalyst [(RuCl2(H2ITapMe2)(=CH–2-(2-PrO)-C6H4))2+ (OTf−)2] (Ru-2, H2ITapMe2 = 1,3-bis(2’,6’-dimethyl-4’-trimethylammoniumphenyl)-4,5-dihydroimidazol-2-ylidene, OTf− = CF3SO3−) based on a dicationic N-heterocyclic carbene (NHC) ligand was prepared. The reactivity was tested in ring opening metathesis polymerization (ROMP) under biphasic conditions using a nonpolar organic solvent (toluene) and the ionic liquid (IL) 1-butyl-2,3-dimethylimidazolium tetrafluoroborate [BDMIM+][BF4−]. The structure of Ru-2 was confirmed by single crystal X-ray analysis.
Keywords: biphasic catalysis; ionic initiators; recycling; ROMP; ruthenium

(untitled) - Gallivan, J. P.; Jordan, J. P.; Grubbs, R. H. (Tetrahedron Lett., 2005)

(untitled) - Hong, S. H.; Grubbs, R. H. (J. Am. Chem. Soc., 2006)

(untitled) - Jordan, J. P.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Kirkland, T. A.; Lynn, D. M.; Grubbs, R. H. (J. Org. Chem., 1998)

(untitled) - Lynn, D. M.; Mohr, B.; Grubbs, R. H. (J. Am. Chem. Soc., 1998)

(untitled) - Lynn, D. M.; Mohr, B.; Grubbs, R. H. (Polym. Prepr. (Am. Chem. Soc., Div. Polym. Chem.), 1998)

(untitled) - Lynn, D. M.; Mohr, B.; Grubbs, R. H.; Henling, L. M.; Day, M. W. (J. Am. Chem. Soc., 2000)

(untitled) - Mohr, B.; Lynn, D. M.; Grubbs, R. H. (Organometallics, 1996)

(untitled) - Wagaman, M. W.; Grubbs, R. H. (Macromolecules, 1997)

(untitled) - Klučiar, M.; Grela, K.; Mauduit, M. (Dalton Trans., 2013)

(untitled) - Autenrieth, B.; Frey, W.; Buchmeiser, M. R. (Chem. – Eur. J., 2012)

(untitled) - Autenrieth, B.; Anderson, E. B.; Wang, D.; Buchmeiser, M. R. (Macromol. Chem. Phys., 2013)

(untitled) - Autenrieth, B.; Willig, F.; Pursley, D.; Naumann, S.; Buchmeiser, M. R. (ChemCatChem, 2013)

(untitled) - Ferraz, C. P.; Autenrieth, B.; Frey, W.; Buchmeiser, M. R. (ChemCatChem, 2014)

(untitled) - Zhao, J.; Wang, D.; Autenrieth, B.; Buchmeiser, M. R. (Macromol. Rapid Commun., 2015)

(untitled) - Skowerski, K.; Szczepaniak, G.; Wierzbicka, C.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Catal. Sci. Technol., 2012)

(untitled) - Skowerski, K.; Wierzbicka, C.; Szczepaniak, G.; Gułajski, L.; Bienieka, M.; Grela, K. (Green Chem., 2012)

(untitled) - Szczepaniak, G.; Kosiński, K.; Grela, K. (Green Chem., 2014)

(untitled) - Kośnik, W.; Grela, K. (Dalton Trans., 2013)

(untitled) - Leuthäußer, S.; Schwarz, D.; Plenio, H. (Chem. – Eur. J., 2007)

(untitled) - Balof, S. L.; P'Pool, S. J.; Berger, N. J.; Valente, E. J.; Shiller, A. M.; Schanz, H.-J. (Dalton Trans., 2008)

(untitled) - Balof, S. L.; Yu, B.; Lowe, A. B.; Ling, Y.; Zhang, Y.; Schanz, H.-J. (Eur. J. Inorg. Chem., 2009)

(untitled) - Krause, J. O.; Wurst, K.; Nuyken, O.; Buchmeiser, M. R. (Chem. – Eur. J., 2004)

(untitled) - Vygodskii, Y. S.; Shaplov, A. S.; Lozinskaya, E. I.; Filippov, O. A.; Shubina, E. A.; Bandari, R.; Buchmeiser, M. R. (Macromolecules, 2006)

(untitled) - Aitken, B. S.; Lee, M.; Hunley, M. T.; Gibson, H. W.; Wagener, K. B. (Macromolecules, 2010)

(untitled) - Takao, K.-i.; Yasui, H.; Yamamoto, S.; Sasaki, D.; Kawasaki, S.; Watanabe, G.; Tadano, K.-i. (J. Org. Chem., 2004)

(untitled) - Endo, K.; Grubbs, R. H. (J. Am. Chem. Soc., 2011)

(untitled) - Jafarpour, L.; Hillier, A. C.; Nolan, S. P. (Organometallics, 2002)